City and Poetry: The Stage and Language - Boccanera, Jorge (2014)
The author explores the relation between city and poetry, regarding to contents of the urban landscape that inspire poetic creation. It specifically examines urban cultural forms, such as infrastructure, speech, customs, social relations, that make up a particular habitat immediately contrasting with the rural landscape: the bucolic setting of the countryside to the overwhelming metropolis. The city has served well to inspire the work of poets such as Lorca, Hemingway and Borges.